1999
DOI: 10.1038/sj.bjp.0702520
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the inhibitory activity of PDE4 inhibitors on leukocyte PDE4 activity in vitro and eosinophil trafficking in vivo

Abstract: Phosphodiesterase (PDE) 4 inhibitors have been shown to inhibit eosinophil PDE4 activity in vitro and accumulation of eosinophils in experimental airways inflammation. However, direct effects on eosinophil trafficking have not been studied in detail and it is not known if activity in vitro translates into efficacy in vivo. In the present study, we compared the activity of five PDE4 inhibitors in vitro and against trafficking of 111In‐eosinophils in cutaneous inflammation in the guinea‐pig. The rank order of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Piclamilast has been reported to be among the most potent PDE4 inhibitors in peripheral tissues in vitro and for displacing [ 3 H]-rolipram binding to brain cerebellar preparations (Cooper et al 1999). It also is 400-fold more potent than rolipram in terms of binding to the HARBS (Zhao et al 2003a).…”
Section: Discussionmentioning
confidence: 96%
“…Piclamilast has been reported to be among the most potent PDE4 inhibitors in peripheral tissues in vitro and for displacing [ 3 H]-rolipram binding to brain cerebellar preparations (Cooper et al 1999). It also is 400-fold more potent than rolipram in terms of binding to the HARBS (Zhao et al 2003a).…”
Section: Discussionmentioning
confidence: 96%
“…Elevated cAMP levels suppress inflammatory cell activation and the release of leukotrienes, PAF, TNFa, cytokines (IL-2, IL-4, IL-5 and IL-8) and eicosanoids [22]. Elevated cAMP through PDE4 inhibition by rolipram also explains the reduction in eosinophils in BALF since rolipram has been shown to inhibit eosinophil trafficking in vivo [39].…”
Section: Discussionmentioning
confidence: 96%
“…PDE4 inhibitors can attenuate neutrophil/eosinophil migration into the lung in models of these diseases (Spina et al, 1998;Torphy et al, 1998;Giembycz, 2000). In particular, it has been demonstrated that rolipram inhibits eosinophil chemotaxis in vitro (Alves et al, 1996;Tenor et al, 1996) and trafficking to sites of inflammation in vivo (Cooper et al, 1999). Rolipram also suppresses many aspects of neutrophil function including adhesion to endothelial cells (Derian et al, 1995).…”
Section: How Can Integrin-induced Fluctuations In Camp Alter Cellularmentioning
confidence: 99%